AN ANALYSIS OF THE URBAN POVERTY IN TAMIL NADU - R.VENKATESH (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Abstract In light of the development of rural areas and the rural residents' migration to cities in pursuit of survival, the urban population is rising. As a result, more and more people are moving to cities like Chennai in search of work that Chennai can support, making cities like Chennai untenable. The only way to solve this issue is to make tiny towns and villages livable places. Most people claim that if they could earn 40% less than they do in Chennai, they would be content to live in small towns and villages.